Social responsibility and scientific research in a private university in Lima, Peru - CHARRY AYSANOA, Juan Marciano (2021)
The article presents the results of the research related to the fulfillment of social responsibility (SR) in scientific research (CI) in the country. It assumes the Interpretative paradigm, Qualitative approach, Hermeneutical design. The sample was made up of five PhD students at a private university in Lima, all with a Master's degree and involved in CI. The technique used was the interview and the instrument a semi-structured interview guide. The study meets criteria of credibility, auditability, transfer and confirmability of the data, which determines the scientificity of the work. The results determine that SR, in general terms, is not fully complied with in the country, mainly due to the capitalist interests of companies and institutions and profit-making purposes, which does not go beyond economic interests, so the population is unprotected in terms of its welfare. CI in the country as a generator of knowledge and seeking the benefit of society, is not being developed in light of the needs of today's society; There is a minimal development, showing a classical academic training, to this is added that the research teachers who contribute to the training of postgraduate students do not have the deserved recognition and receive low remuneration. SR and CI are not profitably linked, nor is their transcendental importance for society evident. Regarding the role of the university,it is concluded that there is passivity in the development of CI with SR.Keywords: Social responsibility, scientific research.